Impact of Digital Marketing Skills on Digital Marketing Performance of Entrepreneurs - Hesham Magd , Venkat Ram Raj Thumiki, (European Economic Letters (EEL), 2023)
In the present study, the relationship between the digital marketing skills of the entrepreneurs and their perceived digital marketing performance was examined by using the factor analysis scores in multiple regression model. The data was collected from 87 independent entrepreneurs selected using the snowball sampling technique. Factor analysis and regression analysis were conducted to evaluate the data. Three factors, representing digital marketing skills, ‘content and promotion’, ‘communication and transactions’, and ‘monitoring and measurement’ were selected as explanatory variables and used for multiple linear regression analysis. It was found that these three factors had significant effect on the perceived digital marketing performance of entrepreneurs in Oman. The research attains significance in the current era of rising digital marketing practices by entrepreneurs.